2011
DOI: 10.4081/ijas.2011.e61
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of inflammatory response phenomena in periparturient dairy cows by the administration of an ω3 rumen protected supplement containing vitamin E

Abstract: The aim of this research was to study the consequences of ω3 fatty acids (FA) administration around calving on inflammatory response and on productive performances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 52 publications
2
12
3
Order By: Relevance
“…The lack of response between OME and CTR as it relates to APP suggest that the administration of omega-3 FA alone in late pregnancy did not exert any significant effect on the inflammatory status of cows around calving. This response does not agree with a previous experiment (Trevisi et al, 2011), in which a better inflammatory status after calving was observed with supplementation of omega-3 FA. However, the discrepancy could be partly attributed to the longer period of omega-3 FA administration (pre-and postcalving) or to the contemporaneous administration of vitamin E in Trevisi et al (2011).…”
Section: Effects Of Omega-3 Fa On the Inflammatory Status And On The contrasting
confidence: 99%
See 1 more Smart Citation
“…The lack of response between OME and CTR as it relates to APP suggest that the administration of omega-3 FA alone in late pregnancy did not exert any significant effect on the inflammatory status of cows around calving. This response does not agree with a previous experiment (Trevisi et al, 2011), in which a better inflammatory status after calving was observed with supplementation of omega-3 FA. However, the discrepancy could be partly attributed to the longer period of omega-3 FA administration (pre-and postcalving) or to the contemporaneous administration of vitamin E in Trevisi et al (2011).…”
Section: Effects Of Omega-3 Fa On the Inflammatory Status And On The contrasting
confidence: 99%
“…The decreased lipomobilization in OME cows is confirmed by the reduced concentration of BHB and the greater of glucose compared with CTR and to OMAS cows. A better postcalving energy status in cows fed a diet enriched in omega-3 FA was previously observed by Ballou et al (2009) and by Trevisi et al (2011). Conversely, Mattos et al (2004) found decreased plasma concentrations of glucose and greater BHB in cows fed omega-3 FA vs. cows fed olive oil, whereas no differences were observed in NEFA.…”
Section: Effects Of Treatments On Energy Metabolismsupporting
confidence: 59%
“…We found few differences in the plasma concentrations of biomarkers of inflammation and oxidative stress with our feed restriction-induced NNB, which is contrary to work with periparturient cows (Bertoni et al, 2008). Increases in FRAP and retinol are positively associated with antioxidant activity (Benzie and Strain, 1996;Trevisi et al, 2011), whereas nitric oxide increases are associated with greater inflammation and oxidative stress (Trevisi et al, 2013). Therefore, the changes in FRAP, retinol, and nitric oxide indicate that our feed restriction model did induce some oxidative stress.…”
Section: Biomarkers Of Inflammation and Oxidative Stresscontrasting
confidence: 61%
“…This marked decrease in the concentration of haptoglobin by d 21 postpartum in ethyl-cellulose RPM-supplemented cows indicates they were able to better control the inflammatory response. Additionally, the higher concentration of plasma albumin, as well as cholesterol and paraoxonase, which are also biomarkers of anti-inflammatory responses, in ethyl-cellulose RPM cows supports the idea that they were under a less pronounced inflammatory state (Trevisi et al, 2011;Grossi et al, 2013). Myeloperoxidase tended (P = 0.15) to be higher in the ethyl-cellulose RPM group compared with control cows.…”
Section: Biomarkers Of Inflammationsupporting
confidence: 53%
“…These results partly reflect the greater DMI in RPM cows during the postpartum period (Batistel et al, 2017). The greater concentrations of those vitamins, together with greater plasma concentration of FRAP, is positively associated with antioxidant activity (Benzie and Strain, 1996;Trevisi et al, 2011). Retinol concentration was not different between groups (P = 0.18).…”
Section: Biomarkers Of Oxidative Stressmentioning
confidence: 84%